Analisis Fatwa Majelis Ulama Indonesia terhadap Perkembangan Produk Keuangan Syariah - Zaki Pradipta Ananda; Adit Pramana (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2024)
This research discusses the role of fatwa of Indonesian Ulema Council (MUI) in the development of Islamic financial products in Indonesia. By using document analysis method and interviews with Islamic scholars and practitioners, this study found that MUI's fatwa has a strategic role in providing sharia legitimacy to various Islamic financial products. However, the main challenge faced is the lack of public understanding of the principles of Islamic finance.